Understanding online shopping intention: the roles of four types of trust and their antecedents. Issue 3 (27th May 2014) - Hsu, Meng-Hsiang; Chuang, Li-Wen; Hsu, Cheng-Se
Abstract : Purpose: – The purpose of this paper is to provide a better picture of factors influencing behavioral decisions in online shopping by identifying different targets of trust and discussing their antecedents and outcomes. Design/methodology/approach: – Online survey data from 242 ihergo members were used to test the proposed model, and structural equation modeling with partial least squares was performed to analyze the measurement and structural models. Findings: – The findings show that the four types of trust identified in this study are critical determinants of perceived risk and attitude. In addition, the majority of the antecedents are found to be associated with their respective types of trust. Research limitations/implications: – The research extends the theory of reasoned action and prior research to discuss four types of consumer trust, as well as their respective antecedents and subsequent consequences. The result is a more descriptive model that better explicates consumers' decision-making processes in online shopping. Practical implications: – Given the intense competition between online shopping sites, web site managers should strive to provide a safe and user-friendly shopping environment. In addition, the vendor can enhance trust by encouraging satisfied customers to provide positive endorsements. Originality/value: – This study is possibly the first of its kind, in identifying the four types of trust and their respective antecedents in the context of an online group-buying auction, and thus serves to enrich the existing literature concerning trust-building factors.